Does infant formula containing synbiotics support adequate growth in infants? A meta-analysis and systematic review of randomized controlled trials. Issue 6 (28th February 2023) - Janmohammadi, Parisa; Nourmohammadi, Zeinab; Fazelian, Siavash; Mirzababaei, Atieh; Alizadeh, Shahab; Zarei, Mahtab; Daneshzad, Elnaz; Djafarian, Kurosh
Abstract: In recent years, several studies have shown that formulas that contain synbiotics, i.e. composed prebiotics and probiotics have been proposed to have a beneficial effect on anthropometric indices. However, the results are inconsistent thus this meta-analysis was performed to assess this effect. PubMed/MEDLINE, Web of Science, SCOPUS, and Embase were systematically searched up to May-2020. Weight gain, length gain, head circumstance gain, weight-for-age z scores, and length-for-age z scores were considered as the outcomes. Weighted mean differences (WMD) with the 95% CI were applied for estimating the combined effect size. Subgroup analysis was performed to specify the source of heterogeneity among studies. Consumption of formulas containing synbiotics did not affect growth significantly in healthy infants (weight gain (WMD = 2.06, 95% CI: − 4.08 to 8.21; p = 0.51), length gain (WMD = − 0.05, 95% CI: − 0.70 to 0.60; p = 0.88), head circumstance (WMD = − 0.28, 95% CI: − 0.66 to 0.11; p = 0.15), on weight-for-age z-scores (WMD = − 0.05, 95% CI: − 0.23 to 0.13; p = 0.57) and length-for-age z-scores (WMD = − 0.16, 95% CI: − 0.50 to 0.19; p = 0.37)). The main results indicate a non-significant increase in infant's growth following synbiotics supplementation of infant formula. Further large-scale studies are warranted to confirm present findings.